Koordinasi Camat Dalam Implementasi Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Pedesaan Di Kecamatan Pasan Kabupaten Minahasa Tenggara - Ratela, Bryan; Rompas, Sonny; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
BSTRACTDistrict head as leaders of districts is one of the principals in the district PNPM that as Trusteesimplementation to villages in the districts. Therefore the Head role in coordinating the implementationof PNPM Mandiri districts. The purpose of this study was to determine how the district headcoordination in the implementation of PNPM Rural in the district Pasan Southeast Minahasa Regency.This study used qualitative methods. The focus of research is camat coordination in planning activitiesand in the implementation of activities funded by PNPM Mandiri. Data sources / informants drawnfrom elements PNPM actors at the district level and village level, as many as 15 people. Collecting datausing interview techniques. While the analysis of data using qualitative analysis techniques interactivemodel of Miles and Hubernan.The results showed: (1) Coordination Head PNPM Mandiri in planning activities carried outeffectively through inter-village meetings (MAD) Dissemination and Proposed Priority MAD discussand rank the proposed activities, and through MAD Determination Proposal for decision making.With the coordination of the planning of these activities so that the activities set out in the villages canfit the needs of local communities; (2) Coordination Head in the implementation of PNPM Mandiriactivities carried out effectively through Early in the District Coordination Meeting, MeetingEvaluation, Monitoring and Auditing, and Reporting. With District head coordination in theimplementation of activities dilaksanakanpada activities so that villages can run orderly, smoothly andsuccessfully.The research results provide the conclusion that the sub-district coordination in the implementation ofPNPM Rural in the district Pasan Southeast Minahasa Regency implemented effectively.Based on the results of this penellian it can be recommended some suggestions: (1) Coordination HeadPNPM Mandiri in planning activities need to be improved. In this case the sub-district must provideguidance and direction effectively against all perpetrators of PNPM Mandiri in the district and in thevillage; (2) Coordination Head in the implementation of PNPM Mandiri still needs to be improved. Inthis case the sub-district should be more frequent visits to villages to monitor, inspect and supervise theimplementation of PNPM Mandiri.Keywords: District head coordination, implementation of PNPM Mandiri